PENERAPAN SISTEM BERBASIS PENGETAHUAN KARYAWAN PADA MEDIA WEBSITE TRAKINDO.CO.ID - Reni Widyastuti (Paradigma, 2018)
Abstract  –  Knowledge sharing is an important stage of knowledge management cycle after the stage of knowledge creation by individuals or groups that interact and connect an organization. Organizations can save and reuse it as an organizational asset through the media website that has characteristics of system quality, service, science / information is good. Employees will be motivated and contribute to the system to share knowledge if it has a conducive organizational culture. This paper investigates the individual behavior of Trakindo employees to be motivated and able to feel the benefits of sharing knowledge. Data was collected by distributing questionnaires to web user respondents ie www.trakindo.co.id with Number of questionnaires 180 packs but questionnaire returned 133 with percentage of 73.88%. Data were analyzed by the Structural Equation Model (SEM) methodology with AMOS software version 24. The results show that knowledge sharing behavior on individuals / employees on the website is influenced by organizational culture dimensions (such as support, management and reward policies, trusts) and system technical characteristics (such as system quality) and knowledge sharing significantly affecting employee personal benefits